Examining the predictive validity of behavior screeners across measures and respondents. Issue 6 (21st March 2020) - Jones, Corey; Graybill, Emily; Barger, Brian; Roach, Andrew T.
Abstract: Through this study we compared different informants and different behavior screening tools that are available to screen for behavioral and emotional risk. We examined screening results from 100 students from a high school with a high achiever's magnet program in the Southeastern United States (school demographics: 71% female and 79% black, non‐Hispanic). This school conducted behavior screening using both teacher‐report via the Student Risk Screening Scale, Internalizing/Externalizing (SRSS‐IE) and student report via the Strengths and Difficulties Questionnaire (SDQ). Nonparametric correlation tests were conducted between the SRSS‐IE and SDQ externalizing and internalizing scores. Generalized linear regression models were created based on the data (demographics, internalizing, and externalizing scores on both screening tools) to model the two count outcomes (office discipline referrals [ODRs] and absences). Diagnostic accuracy metrics were generated from the scores on both the SRSS‐IE and SDQ with the outcome measures (ODRs and absences). Externalizing scores on both screening tools had statistically significant low correlations. The ODR model contained two predictors: externalizing score on the SRSS‐IE and internalizing score on the SDQ, while the absence model contained grade and the externalizing score on the SDQ. The highest accuracy and agreement values were seen between students with elevated risks on both screening measures and ODRs. The results confirmed that teacher and student reporting, as well as different screening tools, will result in some different students being identified. The choice of informant and screening tools should be dependent on the needs and resources of the school.